Comprehensive investigations on printability and thermal performance of cementitious material incorporated with PCM under various conditions. (1st June 2022) - Liu, Zhixin; Li, Mingyang; Kandasamy, Ranjith; Ho, Jin Yao; Wong, Teck Neng; Li, Holden King Ho; Tan, Ming Jen
Highlights: The enhanced building materials are printable, and 28.4% fabrication cost is saved. PCM composite wall thermal performance was studied using Enthalpy porosity method. Heat flux is sensitive to PCM contents, melting temperature, and heating conditions. About 30% heat can be prevented in tropical climate using the developed material. Abstract: Energy consumed in building and construction accounts for 40% of the total end-use energy. To achieve the energy reduction in this area, conventional construction approaches need to be reshaped. To overcome existing challenges, this study explores the use of 3D cementitious material printing (3DCMP) and investigates the printability of these cementitious materials incorporated with the phase change material (PCM). To realize the newly developed composite cementitious materials for real-world applications, we examinate the benefits of utilizing them for building's energy consumption reduction. From our study, we demonstrate, for the first time, the successful fabrication of the PCM composite wall by 3DCMP method. The enthalpy porosity method is then proposed to study the time-dependent thermal performance of the composite wall by modelling the encapsulated PCM and cementitious material as porous and medium, respectively. Our results show the proposed model is reliable in predicting the PCM composite wall thermal performance and demonstrate the composite wall has the potential of smoothing and reducing energy consumption by the building. From our investigation, it is determined that the PCM melting temperature should be chosen based on heating time and heat power density. Additionally, the total cost of precasting a wall by conventional methods with a dimension of 4 m × 0.12 m × 2.8 m (L × W × H) is 28.4% higher than the printing counterpart. Furthermore, the performance enhancements resulted in approximately 30% savings in building energy consumption during the day using plain walls infused with 3% PCM. This study not only demonstrates the potential of fabricating enhanced building materials through the utilization of additive manufacturing technique, but it also provides the guidelines to design PCM composite walls under various operating conditions.